2019
DOI: 10.1111/jgh.14637
|View full text |Cite
|
Sign up to set email alerts
|

Serum Mac‐2‐binding protein glycosylation isomer and risk of hepatocellular carcinoma in entecavir‐treated chronic hepatitis B patients

Abstract: Background and Aim Hepatocellular carcinoma (HCC) can still develop in chronic hepatitis B (CHB) patients receiving antiviral treatment. Serum Mac‐2‐binding protein glycosylation isomer (M2BPGi) is a novel marker for liver fibrosis. We investigated its role on incidence of HCC in entecavir (ETV)‐treated CHB patients. Methods We identified HCC cases diagnosed at ≥ 1 year of ETV treatment. CHB patients without HCC (matched for age, gender, baseline hepatitis B virus‐DNA, and duration of ETV treatment) were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…When the presence or absence of HCC was evaluated after the fibrosis stages were adjusted, no difference in M2BPGi levels was found [58], which was considered to reflect its carcinogenic potential due to fibrosis progression. Longitudinal observational studies have reported that patients with M2BPGi level ≥ 0.71−2.0 have a high risk of HCC development (Table 2) [53,58,[62][63][64][65][66][67][68][69]. In considering the risk of carcinogenesis, the presence or absence of treatment should be considered.…”
Section: Utility Of M2bpgi In Chronic Hepatitis Bmentioning
confidence: 99%
“…When the presence or absence of HCC was evaluated after the fibrosis stages were adjusted, no difference in M2BPGi levels was found [58], which was considered to reflect its carcinogenic potential due to fibrosis progression. Longitudinal observational studies have reported that patients with M2BPGi level ≥ 0.71−2.0 have a high risk of HCC development (Table 2) [53,58,[62][63][64][65][66][67][68][69]. In considering the risk of carcinogenesis, the presence or absence of treatment should be considered.…”
Section: Utility Of M2bpgi In Chronic Hepatitis Bmentioning
confidence: 99%
“…M2BPGi has been used as a liver fibrosis marker for various liver diseases [65], including NAFLD [43,64,66]. Accumulating evidence suggests that higher levels of serum M2BPGi can predict HCC incidence in patients with chronic hepatitis B [67][68][69][70][71][72]. According to a report by Kawanaka et al [73], the carcinogenic rate was as high as 6.8% at 5 years and 21.1% at 10 years in NAFLD cases where M2BPGi was 1.26 or higher, while the rate was as low as 1.7% at 5 years and 1.7% at 10 years in patients with M2BPGi below 1.26 [73].…”
Section: Mac2 Protein Glycosylated Isomermentioning
confidence: 99%
“…Therefore, undetectable HBV DNA may be used as a factor constituting a predictive model for HCC development. Furthermore, previous reports showed that HBsAg, [20][21][22] HBcrAg, [21][22][23] HBV DNA level, 19,24 liver stiffness 25 and M2BPGi [26][27][28][29][30] during treatment were useful for stratification of carcinogenic risk. Future studies are required to determine whether a more accurate carcinogenic risk prediction model could be constructed by combining these scores with PAGE-B.…”
Section: Predictability Of Risk Models For Hcc Developmentmentioning
confidence: 99%